Pengaruh Budaya Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Bank Jatim Cabang Syariah Kediri - Desi Fidiawati Fidiawati; Nur Laely; Meme Rukmini (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the influence of organizational culture and work environment on the performance of Bank Jatim Syariah Kediri Branch employees. This research uses quantitative research methods because the research data is in the form of numbers and analyzed using statistics and meets scientific principles, namely concrete, objective, measurable, rational and systematic. The population in this study were all employees of Bank Jatim, Kediri Syariah Branch, namely 59 people. The sample was also 59 people/respondents. Data collection methods use questionnaires, interviews and documentation studies. Meanwhile, the data analysis method uses validity and reliability tests, classical assumption tests, multiple linear regression tests, partial significance tests (t statistical test), simultaneous significance tests (f statistical test), and coefficient of determination. From the results of this research it can be concluded that: (1) Based on (F-Test) it is known that the Organizational Culture variable and the work environment variable simultaneously have a positive and significant effect on the Performance of Bank Jatim Syariah Kediri Branch Employees. (2) Based on (t-test) the variables Organizational Culture and Work Environment have a positive and significant effect on the Performance of Bank Jatim Syariah Kediri Branch Employees. (3) Based on the calculation of the coefficient of determination (R2), it shows that the relationship between the independent variables Organizational Culture and Work Environment has a fairly close relationship to the Performance of Bank Jatim Syariah Kediri Branch Employees.